Nonlinear buckling behavior of FG-GPLRC cylindrical shell stiffened by spiral FG-GPLRC stiffeners subjected to axial compressive load in thermal environment - Thai, Kieu Quang; Bich, Dao Huy; Phuong, Nguyen Thi; Doan, Cao Van; Minh, Tran Quang (Vietnam Journal of Mechanics, 2025)
This study investigates the nonlinear behavior of functionally graded graphene platelet-reinforced composite (FG-GPLRC) thin cylindrical shells stiffened by orthogonal or spiral FG-GPLRC stiffeners under axial compression. Five graphene platelet (GPL) distribution patterns for shell and stiffeners are considered. The governing equations are formulated based on Donnell shell theory, incorporating geometric nonlinearity of von Karman and the effects of Pasternak elastic foundation. The influence of spiral stiffeners is modeled using an improved Lekhnitskii smeared stiffener technique, considering both mechanical and thermal stresses. Circumferential closed conditions, three-term form of deflection, and the Ritz energy method are employed to derive expressions for the critical buckling load and postbuckling load-deflection curves. The results demonstrate that spiral stiffeners provide superior load-carrying capacity compared to orthogonal stiffeners. Numerical studies also show significant effects of thermal environment, material distribution patterns, geometric parameters, and elastic foundation on the buckling and postbuckling responses of stiffened shells.